China– Sri Lanka And Maldives Relationship And Its Impacts On India - Ganeshalingam, K.T. (Kolkata society for asian studies in collaboration with indian council of world affairs, new delhi and indian council of social science research, eastern regional centre, 2021)
Sri Lanka and the Maldives geo-strategic location caused apprehension to Indian security because of the possibility of the involvement of foreign powers with that countries against India’s strategic and security interests. New Delhi perceives that presence of any foreign powers in the Island nations can possibly sham a serious threat to the security of India, Indian Ocean as well as to regional stability. And the components of the growing India-Sri Lanka Maldives strategic narrative, the real worry for India are growing Chinese activism in the Indian Ocean region. China’s efforts at calming the Indian Ocean rime countries have been a concern for New Delhi. In response, New Delhi has pursued many paths to build link with these neighbors, including bilateral, trilateral, and multi-lateral conversations in the region. Very recently(2020)fourth national security level tri-lateral(India, Maldives and Sri Lanka) maritime security cooperation meeting after joint statement of press release:. The three countries also exchanged views on common security threats and agreed to broad-base cooperation by expanding the scope to improve intelligence sharing and include issues like terrorism, radicalism, extremism,drugs, arms, and human trafficking, money laundering, cyber security and effect of climate change on maritime environment, according to the statement. During the past three decades China emerged as the most important investor of Sri Lanka in financing strategically important infrastructure development projects. Funding the development of Hambantota port and airport, expansion of Colombo port project, building Norochcholai power plant, recently hybrid renewable energy systems in small Islands in Northern Sri lanka, and laying of expressways were mainly carried out with Chinese assistance. China has built the Maldivian Foreign Ministry building as well as a museum, which houses the Ministry of Culture and Heritage. The Chinese have also built several housing projects in Malé, apart from building roads as well as the drainage system in the city. India and China share a border with each other and the contradictions and the conflict between the two countries over this continue unresolved. India, therefore, does not favor the growing close ties China with Sri Lanka and Maldives are involved in activities that will defeat this relationship. Nevertheless, China has friendly established its authority in the backyard of India that are Sri Lanka and Maldives. In this presentation the impact on India as a result of the strengthening China –Maldives and Sri Lanka Relationship, in addition to India’s strategic response is discussed.